DIFERENCIACION ECOLOGICA Y REPRODUCTIVA DE DOS RAZAS HUESPEDES DE RHAGOLETIS CONVERSA (Bréthes) (DIPTERA: TEPHRITIDAE) - Frías L., Daniel (Acta Entomológica Chilena, 2022)
Rhugnletis conversa (Bréthes) is a Chilean species of Tephrilid fly which attacks fruils of native Solanum tomatillo and Solanum mgnim. This species show two host races. An ecological and reproduclive research un natural populations of these two races is the subject of this paper. The results prove that both races offer seasonal differenliation in their populalion distribulion, mating behaviour and oviposition.